ANALYSIS THE EFFECTIVENESS OF CHATGPT IN ENHANCING SECRETARY WRITING SKILL AT CAMPUS ORGANIZATIONS - Juliana Sidauruk; Honey Marbun, Rita Hartati (International Journal of Teaching and Learning, 2025)
This research examines the effectiveness of ChatGPT in improving the writing skills of secretaries in campus organizations. Secretarial roles require high proficiency in written communication, which is essential for drafting reports, emails, and official documents. By integrating ChatGPT as an AI-driven writing assistant, this study seeks to evaluate its potential in enhancing both the quality and efficiency of written tasks. A questionnaire was employed as the primary data collection tool, targeting secretaries from various campus organizations. The results indicate a significant improvement in the accuracy and clarity of written communication, with secretaries reporting a reduction in time spent drafting documents and increased confidence in their writing. The study provides valuable insights into the utility of AI tools like ChatGPT in streamlining secretarial tasks and enhancing professional skills in organizational contexts.